ASSESSMENT OF ARTHROSONOGRAPHIC CHANGES DURING LONG-TERM TERAFLEX THERAPY FOR GONARTHROSIS(3-YEAR FOLLOW-UP) - Marina Stanislavovna Svetlova; I V Kheyfets; Marina Stanislavovna Svetlova; I V Kheifets (Современная ревматология, 2011)
Two hundred and forty-four outpatients with gonarthrosis were examined. The time course of arthrosonographic (the height of the articular cartilage, the volume of intraarticular effusion, the width of the joint cleft, and the degree of osteophytosis) changes were estimated during longterm Teraflex therapy and in control patients. The long-term (3-year) Teraflex therapy was shown to have a restraining impact on the processes of articular cartilage degradation and the progression of articular structural changes and to exert an anti-inflammatory effect.